Impact of MET alterations on targeted therapy with EGFR-tyrosine kinase inhibitors for EGFR-mutant lung cancer - Zhe Zhang; Sen Yang; Qiming Wang (BMC, 2019)
Abstract EGFR-tyrosine kinase inhibitors (EGFR-TKIs) have achieved remarkable outcomes in the treatment of patients with EGFR-mutant non-small-cell lung cancer, but acquired resistance is still the main factor restricting their long-term use. In addition to the T790 M mutation of EGFR, amplification of the MET (or c-MET) gene has long been recognized as an important resistance mechanism for first- or second-generation EGFR-TKIs. Recent studies suggest that a key mechanism of acquired resistance to third-generation EGFR-TKIs (such as osimertinib) may be MET amplification and/or protein overactivation, especially when they are used as a first-line treatment. Therefore, in patients resistant to first-generation EGFR-TKIs caused by MET amplification and/or protein overactivation, the combination of osimertinib with MET or MEK inhibitors may be considered.